CORE TAX: PEMENUHAN KEWAJIBAN PERPAJAKAN YAYASAN JUJUR MINISTRY - Meyliana, Meyliana; carolina, verani; setiana, sinta; erna, erna; silaban, barnabas tridig; aurellia, tan lilyani (Jurnal Likhitaprajna, 2025)
The implementation of the Coretax Administration System starting on January 1, 2025, is part of a major reform in Indonesia’s tax administration system. This system aims to improve efficiency, effectiveness, transparency, and accuracy in the tax reporting and payment process through automation and data integration. Referring to Minister of Finance Regulation Number 81 of 2024, Coretax becomes a new system that must be understood by all taxpayers, including social foundations such as Jujur Ministry under the auspices of Yayasan Terobosan Baru Indonesia. To support this transition, lecturers and students from the Accounting Study Program at Maranatha Christian University conducted a community service activity in the form of a one-day seminar that included a Coretax usage socialization session followed by a Q&A segment. This activity aimed to provide practical education on the procedures for using Coretax, such as tax ID (NPWP) registration, account creation, as well as the steps for tax withholding and reporting. The results of the activity showed an increase in participants’ understanding of tax obligations and the Coretax system. It is concluded that collaboration between academics and the community plays a vital role in supporting the optimal implementation of the new tax system.